Cerebrovascular Thromboprophylaxis in Mice by Erythrocyte-Coupled Tissue-Type Plasminogen Activator - Danielyan, Kristina; Ganguly, Kumkum; Ding, Bi-Sen; Atochin, Dmitriy; Zaitsev, Sergei; Murciano, Juan Carlos; Huang, Paul L.; Kasner, Scott E.; Cines, Douglas B.; Muzykantov, Vladimir R. (My University, 2008)
Background¿ Cerebrovascular thrombosis is a major source of morbidity and mortality after surgery, but thromboprophylaxis in this setting is limited because of the formidable risk of perioperative bleeding. Thrombolytics (eg, tissue-type plasminogen activator [tPA]) cannot be used prophylactically in this high-risk setting because of their short duration of action and risk of causing hemorrhage and central nervous system damage. We found that coupling tPA to carrier red blood cells (RBCs) prolongs and localizes tPA activity within the bloodstream and converts it into a thromboprophylactic agent, RBC/tPA. To evaluate the utility of this new approach for preventing cerebrovascular thrombosis, we examined the effect of RBC/tPA in animal models of cerebrovascular thromboembolism and ischemia.Methods and Results¿ Preformed fibrin microemboli were injected into the middle carotid artery of mice, occluding downstream perfusion and causing severe infarction and 50% mortality within 48 hours. Preinjected RBC/tPA rapidly lysed nascent cerebral thromboemboli, providing rapid, durable reperfusion and reducing morbidity and mortality. These beneficial effects were not achieved by preinjection of tPA, even at a 10-fold higher dose, which increased mortality from 50% to 90% by 10 hours after embolization. RBC/tPA injected 10 minutes after tail amputation to simulate postsurgical hemostasis did not cause bleeding from the wound, whereas soluble tPA caused profuse bleeding. RBC/tPA neither aggravated brain damage caused by focal ischemia in a filament model of middle carotid artery occlusion nor caused postthrombotic hemorrhage in hypertensive rats.Conclusions¿ These results suggest a potential RBC/tPA utility as thromboprophylaxis in patients who are at risk for acute cerebrovascular thromboembolism.